Implementasi Kebijakan Program Keluarga Harapan (PKH) di Desa Yosonegoro Kabupaten Gorontalo - Djafar, Nurul Anggraini; Mozin, Sri Yulianty; Ilato, Rosman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Implementation of the Family Hope Program (PKH) Policy in Yosonegoro Village, Gorontalo Regency. Bachelor’s Degree Program in Public Adminisration,, Department of Public Administration, Faculty of Social Sciences, Universitas Negeri Gorontalo. The Prancipal Supervisor is I Dr. H. Rosman Ilato, M.Pd and supervisor II Dr. SriYulianty Mozin, ST, MPA. This research aims to understand how the implementation of the Family Hope Program (PKH) policy is carried out in Yosonegoro Village, Gorontalo Regency, in terms of objectives and targets/standards, resources, characteristics of the implementing organisation, inter-organizational communication, and the attitude of the implementers. This research method uses a descriptive approach with qualitative data analysis. The data collection techniques used are observation, interviews, documentation. Based on the research results in the field, the implementation of the Family Hope Program (PKH) policy in Yosonegoro Village, Gorontalo Regency, has been implemented in accordance with Minister of Social Affairs Regulation No. 1 of 2018 concerning the Family Hope Program (PKH). In detail, the implementation is observed from the aspects of objectives and targets/standards, resources, characteristics of the implementing organisation, inter- organizational communication, and the attitude of the implementers. However, there are still some problems found during the implementation, such as uneven assistance distribution, lack of communication and coordination between policy implementers at the sub-district level, and various issues related to human resources, budget resources, facilities and infrastructure, and the attitude of implementers. To conclude, the implementation of the Family Hope Program (PKH) policy in Yosonegoro Village, Gorontalo Regency, has not been carried out optimally according to the existing regulations. Several aspects still need to be improved and enhanced, including objectives and targets/standards, resources, characteristics of implementing organisation, inter- organizational communication, and the attitude of the implementers.